PERAN GURU DALAM MENUMBUHKAN KARAKTER MANDIRI PADA SISWA TUNARUNGU KELAS III SDLB DAN TKLB DI SEKOLAH LUAR BIASA AUTIS KOTA PONTIANAK - Nisari, Ita; Rustiyarso, Rustiyarso; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This study aims to determine the role of teachers in developing independent character in deaf students in special schools Autis, Pontianak.City The general problem of this study is how the role of the teacher in developing independent character in deaf students in special schools Autism?The sub problem of this research is how the teacher as a communicator? how does the teacher as a motivator in growing independent character in deaf students ?. The research method is a qualitative approach with descriptive methods. Data collection techniques used observation, interviews, documentation,Data collection tools used are observation guides, interview guides, and field notebooks. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The informant is the teacher with the initials JH and MR. The results of the teacher's research as a communicator and motivator show that deaf students are confident, safe, comfortable, happy when they talk about their activities at home so that there are no differences in gaps between students and informants then students understand and understand excited again in learning after the informants provide inspirational advice and encouragement, students can do the task well and confidently after being guided and students mutual respect and respect for their peers, and pray before and after both in learning and extracurricular. Keywords: Teacher Role, Independent Character, Students with Special Needs (Deaf)